Reason and Education
288 p.
Keywords: Israel Scheffler is the pre-eminent philosopher of education in the English-speaking world today. This volume collects seventeen original, invited papers on Scheffler's philosophy of education by scholars from around the world. The papers address the wide range of topics that Scheffler's work in philosophy of education has addressed, including the aims of education, cognition and emotion, teaching, the language of education, science education, moral education, religious education, and human potential. Each paper is followed by a response from Scheffler himself. The collection is essential reading for anyone concerned with contemporary scholarship in philosophy of education, or with the place of this singularly important author in it.